2013
DOI: 10.5606/tjr.2012.041
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sexual Functions in Male Patients with Ankylosing Spondylitis Compared with Healthy Controls

Abstract: Amaç: Bu çalışmada, ankilozan spondilitin (AS), erkek hastalarda seksüel fonksiyon üzerindeki etkisi, araştırıldı, sonuçlar sağlıklı erkek kontrollerle karşılaştırıldı ve hastalık ile ilgili değişkenlerle olan ilişkisi belirlendi. Objectives: This study aims to investigate the impact of ankylosing spondylitis (AS) on sexual functions in male patients, to compare the results with healthy male controls, and to identify the associations with disease-related variables. Hastalar ve yöntemler: Patients and methods:A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…A person with a high self-esteem has a positive evaluation of himself or herself and is able to recognize his/her strengths (28). We identified only one study that focused on selfesteem level in AS patients (25). Similar to our study, that study found lower self-esteem and significantly higher levels of depression, anxiety and alexithymia in AS patients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A person with a high self-esteem has a positive evaluation of himself or herself and is able to recognize his/her strengths (28). We identified only one study that focused on selfesteem level in AS patients (25). Similar to our study, that study found lower self-esteem and significantly higher levels of depression, anxiety and alexithymia in AS patients.…”
Section: Discussionsupporting
confidence: 83%
“…In one study using the HADS tool, Baysal et al (8) reported significantly higher anxiety scores among AS patients but no significantly difference in depression scores versus control group. Studies have looked at other parameters such as quality of life (6), disability (5), sexual dysfunction (25), and alexithymia (26) in addition to anxiety and depression and found considerable impairment in these areas. As expected, we observed significantly higher scores for anxiety and depression in AS patients versus healthy control group in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The search strategy returned 2100 unique citations of which 55 (2.6%) (7)(8)(9)19,22,27,(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(115)(116)(117)(118)(119)(120)(121) met the inclusion criteria (Figure 1). Descriptive characteristics of the 55 included studies are summarised in Table 1.…”
Section: Search Results and Description Of Included Studiesmentioning
confidence: 99%
“…Descriptive characteristics of the 55 included studies are summarised in Table 1. Of the included studies, 50 (90.1%) were quantitative, (7,9,19,27,(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)79,81,82,(84)(85)(86)(87)(88)(90)(91)(92)(93)(94)(96)(97)(98)(99)(100)(101)(102)(115)(116)(117)(118)(119)(120)(121) five (9.1%) were qualitative (77...…”
Section: Search Results and Description Of Included Studiesmentioning
confidence: 99%
“…1 . One study in which the data were presented as the median (minimum-maximum) was excluded ( 17 ). According to the selection criteria defined in Materials and methods, the meta-analysis finally included five articles, involving a total of 484 participants of which 232 were patients with AS.…”
Section: Resultsmentioning
confidence: 99%